A two-dimensional IGZO nanosheet material and preparation method thereof
The preparation of two-dimensional sheet-like IGZO nanosheets by sol-gel method solves the problems of agglomeration and uneven size of IGZO nanoparticles in the prior art, improves the yield and dispersion of nanosheets, enhances the film performance, and achieves efficient batch production.
Patent Information
- Application Number
- CN202310055394.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-01-18
AI Technical Summary
The agglomeration and uneven size problems of IGZO nanoparticles in the prior art lead to the need to add a dispersant in the early stage of formulating the ink, which reduces the performance of the final IGZO film.
Two-dimensional sheet-shaped IGZO nanosheets were prepared by sol-gel method. The indium salt, gallium salt and zinc salt were dissolved in water and alkaline additives were added to make the three salts co-precipitate. After the steps of heat treatment, washing, drying and high-temperature sintering, the sheet-shaped IGZO nanosheets were obtained.
The yield and dispersion of IGZO nanosheets are improved, their dispersion ability in solvents is enhanced, the loss of film performance is reduced, and the efficient production of batch thin film semiconductor functional modules is achieved.
Smart Images

Figure HDA0004060479060000011 
Figure HDA0004060479060000012 
Figure HDA0004060479060000021
Abstract
Description
Technical Field
[0001] The invention relates to a material preparation method, and in particular to a two-dimensional lamellar IGZO semiconductor material and a preparation method thereof. Background Art
[0002] Indium gallium zinc oxide (IGZO) is an n-type semiconductor metal oxide composed of three compounds, In2O3, Ga2O3 and ZnO, in different proportions. It has the advantages of high mobility, low off-state current, wide band gap (~3.5eV), etc., and is an ideal semiconductor material for the preparation of flexible electronic products. Attaching a layer of IGZO on a flexible substrate is an important step in further processing flexible electronic devices such as thin film transistors, inverters and other devices. There are many methods for preparing IGZO thin films, mainly magnetron sputtering, pulsed laser deposition, sol-gel, chemical vapor deposition, atomic layer deposition, pulsed DC magnetron sputtering, etc. Among them, deposition and sputtering methods are currently only prepared by sputtering and vapor deposition of IGZO in the preparation of display devices due to their high cost. The sol-gel method requires low-temperature reaction to adapt to the characteristics of organic thin film substrates that are not resistant to high temperatures, and is still in the laboratory stage. In recent years, the printable ink method has attracted widespread attention in recent years due to its advantages of high-speed production and low cost, by first preparing nano-IGZO and then dispersing IGZO into a solvent system. For example, the OLED-TFT produced by Huaxing Optoelectronics through inkjet printing can reduce production costs (CN201710777726.XOLED-TFT substrate and its manufacturing method, display panel). The inkjet printing technology forms the organic emission pattern of OLED, which can save a yellow light process. However, due to the large number of display panels, different process flows are still required for different links. The process of preparing the IGZO semiconductor layer still uses chemical vapor deposition, which is less efficient.
[0003] Gyoujin Cho et al. obtained nano-IGZO particles by sol-gel method, ball milling after sintering, and centrifugation (Adv. Electron. Mater. 2018, 1800078). The above work shows the possibility of preparing ink by nano-IGZO and further processing IGZO film. However, due to problems such as particle agglomeration and uneven particle size, it is necessary to introduce ultrasound, ball milling, centrifugation and other processes in the early stage of ink preparation, and the yield is not high; and due to problems such as agglomeration and uneven size, dispersants need to be added during the ink preparation process, resulting in the problem of decreased performance of the final IGZO film. Summary of the invention
[0004] Due to the problems of agglomeration and uneven size in the prior art, it is necessary to add a dispersant during the ink preparation process, which reduces the performance of the final IGZO film. In order to solve the above technical problems:
[0005] The present invention provides a two-dimensional flaky IGZO nanosheet, wherein the IGZO nanosheet is a two-dimensional structure, wherein the diameter of the nanosheet is 100nm-5μm, and the thickness is less than 100nm. Preferably, the diameter of the nanosheet is 100nm-2μm, and the thickness is less than 80nm; more preferably, the diameter of the nanosheet is 100nm-1μm, and the thickness is less than 50nm.
[0006] The present invention further provides a method for preparing a two-dimensional flaky IGZO nanosheet, comprising the following steps:
[0007] (1) adding indium salt, gallium salt and zinc salt into a solvent respectively to form a metal salt solution;
[0008] (2) after the three metal salt solutions described in (1) are uniformly mixed, an alkaline additive is added thereto;
[0009] (3) placing the solution obtained in step (3) into an oven for heat treatment to obtain an IGZO precursor solution, wherein the heat treatment temperature is 60-130° C.;
[0010] (4) washing and drying to obtain IGZO precursor powder;
[0011] (5) Sintering the IGZO precursor powder obtained in step (4) to obtain IGZO nanosheets, wherein the sintering temperature is 800-1300° C.
[0012] Furthermore, in the above technical solution, in step (1), the solvent is water; the indium salt is a water-soluble indium salt; the gallium salt is a water-soluble gallium salt; and the zinc salt is a water-soluble zinc salt.
[0013] Furthermore, in the above technical solution, in step (1), the indium salt includes but is not limited to one or more water-soluble salts such as indium nitrate, indium chloride, indium sulfate, indium acetate, etc., and the concentration of the indium salt solution is 0.005 to 0.5M.
[0014] Furthermore, in the above technical solution, in step (1), the gallium salt includes but is not limited to one or more water-soluble salts such as gallium nitrate, gallium chloride, gallium sulfate, and gallium acetate, and the concentration of the gallium salt solution is 0.005 to 0.5M.
[0015] Furthermore, in the above technical solution, in step (1), the zinc salt includes but is not limited to one or more water-soluble salts such as zinc nitrate, zinc chloride, zinc sulfate, zinc acetate, etc., and the concentration of the zinc salt solution is 0.005 to 0.5M.
[0016] Furthermore, in the above technical solution, in step (2), the alkaline additive includes one or a mixture of strong base, weak base or alkaline organic matter; and the pH of the solution after adding the alkaline additive is 4 to 9.
[0017] Furthermore, in the above technical solution, in step (2), the strong base is sodium hydroxide or potassium hydroxide; the weak base is aqueous ammonia; and the alkaline organic matter is ethanolamine or ethylenediamine.
[0018] Furthermore, in the above technical solution, in step (3), the heat treatment time is greater than or equal to 30 minutes.
[0019] Furthermore, in the above technical solution, in step (4), the drying is one of air drying, freeze drying and spray drying; preferably, the drying is freeze drying.
[0020] Furthermore, in the above technical solution, in step (5), the sintering time is greater than or equal to 30 minutes.
[0021] The present invention further provides an application of IGZO nanosheets, which can be dispersed in a suitable solvent, such as dimethyl sulfoxide, N-methylpyrrolidone, ethylene glycol and the like, and can be used for the preparation of n-type semiconductors for printing / inkjet printing or the production of thin film semiconductor functional modules after processing.
[0022] The present invention adopts a sol-gel method, including stirring and dissolving indium salt, gallium salt and zinc salt in water, adding alkaline additives to make the three salts co-precipitate, heat treating in an oven to react to obtain an IGZO precursor, washing and drying to obtain precursor powder, and sintering the powder at high temperature to form IGZO nanosheets.
[0023] (1) Indium salt, gallium salt and zinc salt are added into water to form an aqueous solution, wherein the concentration of each salt is 0.005 to 0.5 M. The salts include water-soluble salts such as nitrates, chlorides, sulfates and acetates.
[0024] (2) The alkaline additives added include common strong bases such as sodium hydroxide and potassium hydroxide, weak bases such as ammonia, ethanolamine, ethylenediamine, or alkaline organic substances, or a mixture of one or more of them. The pH after adding and stirring to stabilize is 4 to 9.
[0025] (3) The heat treatment temperature in the oven is 60-130°C, and the treatment time is greater than or equal to 30 minutes.
[0026] (4) Drying methods include drying, freeze drying, and spray drying.
[0027] (5) The sintering temperature is 800-1300°C and the sintering time is greater than or equal to 30 minutes.
[0028] (6) The diameter of the IGZO flakes after precursor and sintering is between 100nm and 5μm, and the flake thickness is <100nm.
[0029] Beneficial effects of the present invention
[0030] The IGZO obtained by the present invention has a flake diameter between 100nm and 1μm, and a high yield (>90%) of flake products with a flake thickness of <30nm. Therefore, it can be better dispersed in various solvents to prepare n-type semiconductor inks for printing / inkjet printing, and carry out subsequent batch production of thin-film semiconductor functional modules. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope morphology image of the dried IGZO precursor powder prepared in Example 1.
[0032] Figure 2 This is a scanning electron microscope morphology image of the IGZO sintered product prepared in Example 1.
[0033] Figure 3 This is a scanning electron microscope morphology image of the IGZO sintered product prepared in Example 5.
[0034] Figure 4 This is a scanning electron microscope morphology image of the IGZO sintered product prepared in Example 6.
[0035] Figure 5 This is a scanning electron microscope morphology image of the IGZO sintered product prepared in Comparative Example 1.
[0036] Figure 6 This is a scanning electron microscope morphology image of the IGZO sintered product prepared in Comparative Example 2.
[0037] Figure 7 This is a picture of the dispersion effect of the IGZO nanosheets prepared in Example 1 after being left in a pure solvent for 48 hours. DETAILED DESCRIPTION
[0038] The present invention adopts a sol-gel method, including stirring and dissolving indium salt, gallium salt and zinc salt in water, adding alkaline additives to make the three salts co-precipitate, heat treating in an oven to react to obtain an IGZO precursor, washing and drying to obtain precursor powder, and sintering the powder at high temperature to form IGZO nanosheets.
[0039] The specific steps include:
[0040] (1) Indium salt, gallium salt and zinc salt are added into water to form an aqueous solution, wherein the concentration of each salt is 0.005 to 0.5 M. The indium salt, gallium salt and zinc salt include water-soluble salts such as nitrate, chloride, sulfate and acetate, and the concentration of the salt solution is 0.005 to 0.5 M.
[0041] (2) The alkaline additives added include common strong bases such as sodium hydroxide and potassium hydroxide, weak bases such as ammonia, ethanolamine, ethylenediamine, or alkaline organic substances, or a mixture of one or more of them. The pH after adding and stirring to stabilize is 4 to 9.
[0042] (3) The heat treatment temperature in the oven is 60-130°C, and the treatment time is greater than or equal to 30 minutes.
[0043] (4) washing and drying to obtain IGZO precursor powder, wherein the washing method is multiple centrifugation and filtration, and the drying method is one of freeze drying, oven drying, and spray drying.
[0044] (5) The sintering temperature is 800-1300°C, and the sintering time is greater than or equal to 30 minutes.
[0045] (6) Precursor and sintered IGZO nanosheets.
[0046] Embodiment 1:
[0047] Indium chloride, gallium nitrate, and zinc chloride are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.1M, 0.1M, and 0.15M, respectively. Ethylenediamine is slowly added dropwise to precipitate the solution, so that the pH value is stabilized at 7.5-8 after stirring. The reaction solution is then heat-treated in an oven at 80°C for 4 hours. The obtained IGZO precursor is washed and freeze-dried. The powder obtained by freeze-drying is sintered at 1100°C in a tube furnace for 2 hours to obtain IGZO nanosheets. The diameter of the nanosheet is 100nm-5μm and the thickness is <80nm.
[0048] Embodiment 2:
[0049] Indium nitrate, gallium nitrate, and zinc acetate are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.05M, 0.05M, and 0.1M, respectively. Ammonia water is slowly added to precipitate the solution, so that the pH value is stabilized at 4-5 after stirring. Then the reaction solution is heat-treated in an oven at 90°C for 3h. The obtained IGZO precursor is washed and then dried in an oven. The dried powder is sintered in a tube furnace at 800°C for 3 hours to obtain IGZO nanosheets. The diameter of the nanosheet is 100nm-3μm and the thickness is <100nm.
[0050] Embodiment 3:
[0051] Indium chloride, gallium sulfate, and zinc chloride are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.005M, 0.01M, and 0.007M, respectively. A mixed solution of ethanolamine and NaOH is slowly added dropwise to precipitate the solution, so that the pH value is stabilized at 8 to 9 after stirring. The reaction solution is then heat-treated in an oven at 130°C for 2 hours. The obtained IGZO precursor is spray-dried after washing, and the powder obtained by spray drying is sintered at 1300°C in a tube furnace for 2 hours to obtain IGZO nanosheets. The diameter of the nanosheet is 100nm to 2μm, and the thickness is <50nm.
[0052] Embodiment 4:
[0053] Indium nitrate, gallium chloride, and zinc nitrate are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.5M, 0.5M, and 0.5M, respectively. A mixture of ammonia water and KOH with a molar concentration ratio of 1:1 is slowly added to precipitate the solution, so that the pH value is stabilized at 6-7 after stirring. The reaction solution is then heat-treated in an oven at 60°C for 4 hours. The obtained IGZO precursor is washed and dried in an oven. The dried powder is sintered at 1000°C in a tube furnace for 2 hours to obtain IGZO nanosheets. The diameter of the nanosheet is 100nm-3μm and the thickness is <80nm.
[0054] Embodiment 5:
[0055] Indium chloride, gallium nitrate, and zinc chloride are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.1M, 0.1M, and 0.15M, respectively. Ethylenediamine is slowly added dropwise to precipitate the solution, so that the pH value is stabilized at 7.5-8 after stirring. The reaction solution is then heat-treated in an oven at 80°C for 4 hours. The obtained IGZO precursor is washed and oven-dried. The powder obtained by freeze-drying is sintered at 1100°C in a tube furnace for 2 hours to obtain IGZO nanosheets. The diameter of the nanosheet is 100nm-2μm and the thickness is <50nm.
[0056] Embodiment 6:
[0057] Indium nitrate, gallium chloride, and zinc chloride are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.04M, 0.04M, and 0.08M, respectively. Ammonia water is slowly added to precipitate the solution, so that the pH after stirring is stabilized at 6-8. The reaction solution is then heat-treated in an oven at 90°C for 4 hours. The obtained IGZO precursor is washed and freeze-dried. The freeze-dried powder is sintered at 1100°C in a tube furnace for 3 hours to obtain IGZO nanosheets. The nanosheets have a diameter of 100nm to 1μm and a thickness of <50nm.
[0058] Embodiment 7:
[0059] Indium chloride, gallium chloride, and zinc chloride are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.01M, 0.02M, and 0.03M, respectively. Ethanolamine is slowly added dropwise to precipitate the solution, so that the pH value is stabilized at 5-6 after stirring. The reaction solution is then heat-treated in an oven at 70°C for 3 hours. The obtained IGZO precursor is spray-dried after washing, and the dried powder is sintered at 900°C in a tube furnace for 2 hours to obtain IGZO nanosheets. The diameter of the nanosheet is 100nm-3μm and the thickness is <50nm.
[0060] Comparative Example 1
[0061] Indium chloride, gallium nitrate and zinc chloride are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.1M, 0.1M and 0.15M, respectively. Ethylenediamine is slowly added dropwise to precipitate the solution so that its pH is stabilized at 9.5 after stirring. The reaction solution is then heat-treated in an oven at 80°C for 4 hours. The obtained IGZO precursor is washed and freeze-dried. The freeze-dried powder is sintered at 1100°C in a tubular furnace for 2 hours to obtain an IGZO product.
[0062] Comparative Example 2
[0063] Indium chloride, gallium nitrate and zinc chloride are stirred and dissolved in water to form aqueous solutions with molar concentrations of 0.6M, 0.6M and 0.8M, respectively. Ethylenediamine is slowly added dropwise to precipitate the solution so that its pH value is stabilized at 7.5-8 after stirring. The reaction solution is then heat-treated in an oven at 80°C for 4 hours. The obtained IGZO precursor is washed and freeze-dried. The freeze-dried powder is sintered at 1100°C in a tubular furnace for 2 hours to obtain an IGZO product.
[0064] Figure 1 The morphology of the IGZO precursor powder sample obtained by the preparation method described in Example 1 is mainly a lamellar structure, which forms a regular and uniform lamellar structure IGZO product after sintering ( Figure 2 ), the IGZO with a lamellar structure has a large size in the x and y axes, but a small size in the z axis, so it can still be well dispersed in a suitable solvent, which is convenient for subsequent device processing. In addition, due to its large x and y axis dimensions. Compared with nanoparticles that can also be dispersed in solvents, it can increase the microscopic contact area, reduce the contact resistance, and improve the carrier mobility of the film. At the same time, when the pH value of the solution after adding the alkaline additive in Comparative Example 1 is increased and the concentrations of indium chloride, gallium nitrate, and zinc chloride solutions are increased in Comparative Example 2, Figure 5 and Figure 6 It can be seen that the IGZO product with a lamellar structure cannot be obtained, and its shape is similar to a spherical or nearly spherical and lamellar mixed morphology. The IGZO nanosheets prepared in Example 1 are dispersed in ethylene glycol, such as Figure 7The solution shown showed no obvious sedimentation after 48 hours.
Claims
1. An application of a two-dimensional IGZO nanosheet, characterized in that: IGZO nanosheets are dispersed in a solvent and processed for use in the preparation of n-type semiconductors for printing / inkjet printing or in the production of thin-film semiconductor functional modules; The two-dimensional IGZO nanosheet has a diameter of 100 nm to 1 μm and a thickness of <50 nm; The preparation method of IGZO nanosheets comprises the following steps: (1) Add indium salt, gallium salt and zinc salt into the solvent respectively to form a metal salt solution with a concentration of 0.005~0.5M; (2) After the three metal salt solutions described in (1) are uniformly mixed, an alkaline additive is added thereto, and the pH of the solution after the addition of the alkaline additive is 4 to 9; (3) placing the solution obtained in step (2) in an oven for heat treatment to obtain an IGZO precursor solution, wherein the heat treatment temperature is 60-130° C.; (4) washing and drying to obtain IGZO precursor powder; (5) Sintering the IGZO precursor powder obtained in step (4) to obtain IGZO nanosheets, wherein the sintering temperature is 800-1300° C.
2. The use according to claim 1, characterized in that: In step (1), the solvent is water; the indium salt is a water-soluble indium salt; the gallium salt is a water-soluble gallium salt; the zinc salt is a water-soluble zinc salt; the indium salt includes one or more of indium nitrate, indium chloride, indium sulfate, and indium acetate; the gallium salt includes one or more of gallium nitrate, gallium chloride, gallium sulfate, and gallium acetate; the zinc salt includes one or more of zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate.
3. The use according to claim 1, characterized in that: In step (2), the alkaline additive includes one or a mixture of strong base, weak base or alkaline organic matter.
4. The use according to claim 3, characterized in that: In step (2), the strong base is sodium hydroxide or potassium hydroxide; the weak base is aqueous ammonia; and the alkaline organic matter is ethanolamine or ethylenediamine.
5. The use according to claim 1, characterized in that: In step (3), the heat treatment time is greater than or equal to 30 minutes; in step (4), the drying is one of forced air drying, freeze drying, and spray drying; in step (5), the sintering time is greater than or equal to 30 minutes.
Citation Information
Patent Citations
OLED-TFT substrate and manufacturing method thereof, and display panel
CN107369784A
Indium-gallium-zinc oxide powder and preparation method of ceramic target thereof
CN103193262A